PENGATURAN HASIL AGROFORESTRY JABON (Neolamarckia cadamba Miq.) DAN KAPULAGA (Amomum compactum) DI KECAMATAN PAKENJENG, GARUT, JAWA BARAT - Yonky Indrajaya; M Siarudin (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
Agroforestry may contribute to short and long term income for farmers. Agroforestry of caddam-cardamom is widely in practiced Pakenjeng, Garut, West Java. This study aims to analyze the optimal management of  caddam-cardamom agroforest using bio-economic modeling as a modification of  Faustmann model. The results of this study shows that: 1) optimal rotation of  agroforestry caddamcardamom following the biological rotation of  caddam stand is 5 years; 2) the Hartman optimal rotation of  agroforestry caddam-cardamom is 10 years and 3) sensitivity analysis shows: a) the increment in caddam wood price will shorten Hartman rotation; b) the increment in cardamom price will lengthen Hartman rotation and c) the increment in interest rate will shorten Hartman rotation.